ORGANIZING SPACE AND EMPOWERING COMMUNITIES: THE TOURISM CORRIDOR PROGRAM IN BALLAPARANG, MAKASSAR CITY - Yulis, Dewi Nurliasari; M. Ridwan Said Ahmad; Ahmadin (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study aims to determine the factors that influence the success of community empowerment and the impact of the tourism corridor program in Balla Parang Village. The data collection methods used were in-depth interviews, participant observation, and documentation. The data analysis techniques used consisted of three stages, namely data reduction, data presentation and drawing conclusions. The data sources for this study were from residents, tourism corridor program managers, UMKM actors, community leaders and community leaders in Balla Barang Village. The results of this study are that the tourism corridor program in Balla Parang Village has succeeded in empowering the community through active participation, strengthening social cohesion, and involving local culture. The success of the program is supported by targeted government policies, adequate infrastructure, active community participation, and collaboration with the private sector and local communities, thus providing a positive impact on increasing income, food security, social cohesion, and quality of life of the community.